Islam, Muhammadiyah Women and a Sustainable Environment: A Case Study of the Green Aisyiyah Movement - Prayitno, Prayitno; Ifrohayati, Ifrohayati; Lesmana, Lia; Muflihah, Uun; Lie, Raudhatul Hasanah (International Journal of Social Service and Research, 2026)
Global aspirations on climate change are centered on limiting temperature increases to no more than 1.5°C through a net-zero emissions target by 2050. Achieving this requires concrete actions from governments, businesses, and the public, with an emphasis on renewable energy, climate adaptation, and evidence-based policies, driven significantly by youth advocacy. The Green ‘Aisyiyah movement represents an ijtihad (independent reasoning) grounded in Qur’anic and Hadith values that enjoin environmental stewardship. This study aims to understand how the Green ‘Aisyiyah Movement mobilizes women and the broader community to address environmental concerns and mitigate the climate crisis, positioning it as a tangible example of eco-jihad. Employing a qualitative literature review with a case study approach, the research critically analyzes and synthesizes existing academic works on Islamic environmental movements. The findings indicate that Green ‘Aisyiyah is a holistic da'wah effort that integrates spiritual, social, economic, and educational dimensions to foster sustainable behavioral change in society. The movement's prospects are promising, with significant potential for growth and impact in tackling Indonesia's climate crisis, particularly through enhanced internal and external collaboration within the Muhammadiyah network (Pentahelix).